2017
DOI: 10.18632/oncotarget.18274
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing investigation identifies an effective risk score generated by three novel lncRNAs for the survival of papillary thyroid cancer patients

Abstract: Scholars are striving to apply molecular biology involving long non-coding RNA (lncRNA) in the prognostication of papillary thyroid cancer (PTC). However, the clinical role of lncRNAs in the prognostic setting of PTC is still unclear. Herein, a comprehensive inquiry was performed to screen lncRNA expression profiling with 507 PTC patients from The Cancer Genome Atlas RNA-sequencing datasets. A total of 734 lncRNAs were detected to be aberrantly expressed, among which three novel lncRNAs including AC079630.2, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
(42 reference statements)
1
27
0
Order By: Relevance
“…It has been reported that the expression level of lncRNA PAX8-AS1:28 is commonly decreased in patients with neck squamous cell carcinoma, and a higher expression level of lncRNA PAX8-AS1:28 is closely correlated with better survival outcome (18). lncRNA PAX8-AS1:28 expression is also downregulated in patients with PTC (11), and the reduced expression level of lncRNA PAX8-AS1:28 is closely correlated with the poor survival of these patients (19). Consistent with previous studies, in our study, the expression level of PAX8-AS1:28 was found to be lower in PTC tissues and PTC cells than that in adjacent healthy tissues and a normal cell line.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the expression level of lncRNA PAX8-AS1:28 is commonly decreased in patients with neck squamous cell carcinoma, and a higher expression level of lncRNA PAX8-AS1:28 is closely correlated with better survival outcome (18). lncRNA PAX8-AS1:28 expression is also downregulated in patients with PTC (11), and the reduced expression level of lncRNA PAX8-AS1:28 is closely correlated with the poor survival of these patients (19). Consistent with previous studies, in our study, the expression level of PAX8-AS1:28 was found to be lower in PTC tissues and PTC cells than that in adjacent healthy tissues and a normal cell line.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, no survival information of PTC lncRNA was available in the datasets. 37 Therefore, the candidate lncRNAs in the risk sore model were different in our studies, and the three-lncRNA prognostic signature was credible to be a potential biomarker.…”
Section: Discussionmentioning
confidence: 66%
“…Han et al 36 mined the data in the TCGA database, and then 19 significant gene pairs with high diagnostic ability were detected. Luo et al 37 identified a three-lncRNA signature (AC079630.2, CRNDE and CTD-2171N6.1) to predict the PTC patients’ survival. Li et al 38 also provided a four-lncRNA signature (RP11-536N17.1, RP11-508M8.1, AC026150.8 and CTD-2139B15.2) to improve the prognosis prediction of PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] With appropriate treatments such as operation and radioactive iodine ablation, the majority of PTCs have excellent prognoses with an overall survival rate of 97.7% at 5 years. 7,8 Nonetheless, up to 20% patients can suffer locoregional recurrence, and occasionally some progress to aggressive and lethal outcomes. 9 Molecular mechanisms contributing to its carcinogenesis and progression remain obscure.…”
Section: Introductionmentioning
confidence: 99%